Public Service Innovation of the Registration and Identification Card Group, Bang Saphan District, Prachuap Khiri Khan Province - Krainara, Nattapong; Holumyong, Thitima (Legal State Journal, 2024)
This research article aims to evaluate the level of public service innovation of the Registration and Identification Card Group, Bang Saphan District, Prachuap Khiri Khan Province; to compare the public service innovation of the Registration and Identification Card Group, Bang Saphan District, Prachuap Khiri Khan Province categorized by personal characteristics; and to examine the correlation between the management and the public service innovation of the Registration and Identification Card Group. This study employed a quantitative approach. The sample consisted of 398 service recipients of the Registration and Identification Card Group. The research instrument was a 5-point rating scale questionnaire with the Item-Objective Congruence between 0.50-1.00 and reliability of the questionnaire in question stood at 0.93. Statistics used to analyze the data were frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, and Pearson’s product moment correlation coefficient analysis. Findings are as follows: (1) On the analysis of the level of the public service innovation of the Registration and Identification Card Group, it was found at a high level. (2) The comparison between the public service innovation of the Registration and Identification Card Group categorized by personal characteristics was found that people with different age and education had different opinions towards the public service innovation of the Registration and Identification Card Group. (3) The correlation between the management and the public service innovation of the Registration and Identification Card Group was found positive at a relatively low level.